The Spectrum of Endocrine Disorders in Patient Presented with Obstructive Sleep Apnea. A Cross-Sectional Study in Tertiary Care Hospital - Malik, Wajahat Sami; Hayat, Musawer; Azhar, Bilawal; Yasin, Mohammad; Malik, Waseem Sami; Raees, Awais (Indus Journal of Bioscience Research, 2025)
Background: Obstructive sleep apnea has been increasingly acknowledged as a systemic illness with heterogeneous endocrine connections. The detection of concomitant endocrine diseases in patients with obstructive sleep apnea becomes crucial in the overall management and early treatment, particularly in risk groups. Objective: To determine the endocrine disorders in patients presented with obstructive sleep apnea. Study Design: Descriptive cross-sectional study. Duration and Place of Study: The study was conducted from February 2025 to May 2025 at the Department of Pulmonology, Ayub Teaching Hospital, Abbottabad. Methodology: A total of 77 patients aged 20–85 years with confirmed or suspected OSA were enrolled. Diagnosis was based on clinical sleepiness assessment and confirmatory sleep studies in selected cases. Patients underwent detailed history, clinical examination, and relevant investigations to screen for diabetes mellitus, hypothyroidism, acromegaly, metabolic syndrome, and polycystic ovary syndrome. Results: Metabolic syndrome was the most frequent condition, observed in 39 patients (50.6%), followed by hypothyroidism in 34 (44.2%), diabetes mellitus in 25 (32.5%), and acromegaly in 2 (2.6%). PCOS was detected in 2 out of 20 females (10%). Hypothyroidism was significantly more prevalent in urban patients (p=0.001). Conclusion: Endocrine disorders are prevalent among patients with obstructive sleep apnea, underscoring the need for routine endocrine screening to ensure timely diagnosis and holistic management.